Analisa Upper-limb Movement Sequence (UMS) menggunakan Absolute Trajectory Error dan Hand Speed Movement untuk Rehabilitasi Pasca Stroke - Basri Noor Cahyadi; Milkhatussyafa’ah Taufiq; Wan Khairunizam (APIC, 2022)
2019 World Health Organization informed that the two-thirds of stroke patients have a permanent dissability. Disability disorders can affect performance or daily activities such as eating, drinking, wearing clothes, bathing, and others. Disability caused by stroke can be treated by exercising motor function and muscle strength. Studies in upper extremity rehabilitation report that the most important element in the disability recovery process is monitoring the progress of the rehabilitation itself. To monitor and evaluate upper arm rehabilitation, most therapists still rely on clinical assessments based on ordinal scales or charts and are only monitored in terms of the patient's upper arm movement. In this study, we will analyze the rehabilitation movement based on virtual reality games using the Absolute Trajectory Error and Hand Speed ​​Movement methods. While the rehabilitation movement used in this study will apply the Upper-limb Movement Sequence (UMS) method. 5 subjects contributed to data collection over three sessions and five iterations. Their movements were recorded using the Kinect Xbox V2 sensor with 10 Hz sampling data. Mean absolute trajectory error (ATE) and hand speed method were used to analyze arm movements during VR games. Although this study used healthy subjects, 80% of them experienced an increase in movement, and this condition was evidenced by a decrease in ATE values ​​in each session. Trajectory data can be used as the basis for analysis of arm movements during the VR game rehabilitation process, where with these data errors in hand position, hand speed to reach the target, and movement errors can be analyzed more deeply. Moreover, the mean ATE and hand speed movements can show the progress or changes in hand movement during the rehabilitation process clearly.